BRAND IMAGE SEBAGAI MEDIASI PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PONDOK RAOS DI KOTA SOLOK - Eka Hendrayani; Andria Ningsih; Mike Triani; Mustika Lukman Arief (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2022)
Business actors are required to be observant in seeing the opportunities that exist so that later they can continue to compete and survive in the business world. It takes a precise marketing strategy to inform and communicate products and prices to consumers. This study aims to determine the effect of promotion and price on purchasing decisions, whether it has a direct effect on purchasing decisions and promotions and prices have an indirect effect on purchasing decisions through brand image. The sampling technique used was accidental sampling. The population is respondents who often come and visit Pondok Raos. The sample is 196. Data collection methods are observation and questionnaires. The analytical technique used is the Path of SPSS version 17 program. The findings obtained by promotion and price affect purchasing decisions through brand image. Promotion is one of the effective media to inform consumers about products. The conclusion of this study is that brand image has a role as a mediating variable between promotion and price on consumer purchasing decisions in Pondok Raos, Solok City.